Youth employment and joblessness in advanced countries - Blanchflower, David G.; Freeman, Richard B. (Richard Barry), 1943- (NBER Comparative labor markets series., 2000)
The economic status of young people has declined significantly over the past two decades, despite a variety of programs designed to aid new workers in the transition from the classroom to the job market. This ongoing problem has proved difficult to explain. Drawing on comparative data from Canada, Germany, France, Sweden, and the United Kingdom, these papers go beyond examining only employment and wages and explore the effects of family background, education and training, social expectations, and crime on youth employment. This volume brings together key studies, providing detailed analyses of.